2022
DOI: 10.1002/jcla.24467
|View full text |Cite
|
Sign up to set email alerts
|

Development of six immune‐related lncRNA signature prognostic model for smoking‐positive lung adenocarcinoma

Abstract: Background Smoking is one of the most hazardous risk factors for the development of lung adenocarcinoma (LUAD). Many survival and prognosis‐related biomarkers were discovered using database mining. However, the precision of immune‐related long noncoding RNAs (lncRNAs) predictions is insufficient. We identified a novel signature to improve the estimate of smoking‐related LUAD prognosis. Methods The Cancer Genome Atlas database (TCGA) was used to obtain the LUAD lncRNA ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Previous studies also found that these markers can indeed be used as markers of cancer. For example, Zhou et al found that AC002128.2 could be the prognostic biomarker for lung adenocarcinoma [38]. Zhang, Liang, Chen, et al found that AC009237.14 could be the prognostic biomarker for colon adenocarcinoma [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also found that these markers can indeed be used as markers of cancer. For example, Zhou et al found that AC002128.2 could be the prognostic biomarker for lung adenocarcinoma [38]. Zhang, Liang, Chen, et al found that AC009237.14 could be the prognostic biomarker for colon adenocarcinoma [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…AC026355.2 has been reported to play an important role in the prognosis of LUAD [28,29]. AP000695.1 has been reported to play a role in the prognosis of LUAD and gastric cancer [30,31]. ARHGEF26-AS1 is a gene closely related to biological oxidative stress and immune response, which may be a target for the early diagnosis and treatment of Osteoarthritis [32].…”
Section: Discussionmentioning
confidence: 99%
“…This indicate that lncRNAs could potentially function as indicators for predicting, diagnosing, and prognosing lung cancer 16 . While the prognostic significance of lncRNAs has been documented in lung cancer prognosis, 17,18 there has been relatively limited research on the prognostic implications of lncRNAs linked to m6A methylation in LUAD. Hence, it is worth exploring the potential of m6A methylation‐related lncRNAs as novel biomarkers for prognostic evaluation in LUAD patients.…”
Section: Introductionmentioning
confidence: 99%